SENI PEMBELAJARAN MATEMATIKA SEKOLAH DASAR: indonesia - Apri Wahyudi; Adelia Marzuki (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2019)
AbstractLearning mathematics is an artistic value. But it will be a lesson in the "specter" category for some studentswhen math teachers are able to apply fun learning strategies. Need concern for students and carefulness oftheir abilities with high detail. In the learning process and mathematics learning outcomes students are notonly determined by the school, the pattern of the structure and contents of the curriculum, but most aredetermined by the ability of teachers who teach and guide learning that is effective, fun and will be better ableto manage their classes so that student learning is at a level optimal. The teacher must have the courage tochange and perfect himself with the demands of a continuous era, besides that he must dare to examine theshortcomings in all aspects in carrying out their duties, able to provide opportunities for learning in childrenas broad as possible and willingness to perfect various aspects of education. Learning mathematics can be anart when the teacher starts a lesson by arousing student motivation, so students can concentrate at thebeginning of the meeting, and can receive the material delivered by a teacher well. Ending a lesson withspecial, so students always miss the next meeting.Keywords: Art, Mathematics, Elementary SchoolAbstrakPembelajaran matematika merupakan suatu nilai seni. Akan tetapi menjadi pelajaran dengan kategori“momok” bagi sebagian siswa saat guru matematika yang mampu menerapkan strategi pembelajaran yangmenyenangkan. Perlu kepedulian terhadap siswa dan kejelian terhadap kemampuannya dengan detail yangtinggi. Dalam proses belajar dan hasil belajar matematika siswa bukan saja ditentukan oleh sekolah, polastruktur dan isi kurikulumnya, akan tetapi sebagian besar ditentukan oleh kemampuan guru yang mengajardan membimbing belajar yang efektif, menyenangkan dan akan lebih mampu mengelola kelasnya sehinggabelajar para siswa berada pada tingkat optimal. Guru harus berani mengubah dan menyempurnakan dirinyadengan tuntutan zaman yang terus menerus, selain itu juga dia harus berani meneliti kekurangan-kekurangandi segala segi dalam menjalankan tugasnya, mampu memberi kesempatan belajar pada anak yang seluasluasnya dan kesediaan menyempurnakan berbagai aspek pendidikan. Pembelajaran matematika dapat menjadisebuah seni apabila guru memulai suatu pelajaran dengan membangkitkan motivasi siswa, sehingga siswadapat berkonsentrasi pada awal pertemuan, dan dapat menerima materi yang disampaikan seorang gurudengan baik. Mengakhiri suatu pelajaran dengan istimewa, agar siswa selalu merindukan pertemuanberikutnya.Kata Kunci: Seni, Matematika, SD